2010
DOI: 10.1007/s00192-010-1123-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the beneficial effect of antimuscarinics related to motor or sensory changes in the bladder?

Abstract: The mechanism of action of antimuscarinics appears to be a complex interaction of sensory and motor components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
3
17
0
3
Order By: Relevance
“…Complete disclosure of the effect of treatment on BWT requires conduction of additional studies reinforcing outcomes of this study. [16] In conclusion our study data have shown increased BWT in women with OAB both before, and after urination when compared with healthy women. Since measurements using transabdominal US are simple, cheap, and noninvasive which can be applied in outpatient basis, this method should be considered in patients with OAB symptoms.…”
Section: Discussionsupporting
confidence: 55%
“…Complete disclosure of the effect of treatment on BWT requires conduction of additional studies reinforcing outcomes of this study. [16] In conclusion our study data have shown increased BWT in women with OAB both before, and after urination when compared with healthy women. Since measurements using transabdominal US are simple, cheap, and noninvasive which can be applied in outpatient basis, this method should be considered in patients with OAB symptoms.…”
Section: Discussionsupporting
confidence: 55%
“…Некоторые исследователи показали снижение параметров ТСМП у женщин с ГМП и гипер-трофией детрузора на фоне терапии антимускариновыми препаратами [20,21]. Несмотря на то что получены только предварительные результаты, можно предположить веду-щую роль метода для определения эффективности лече-ния пациенток с ГМП.…”
Section: надлобковый доступunclassified
“…[21] выявлена прямая за-висимость показателя ТСД и степени тяжести ургентно-сти. V. Khullar и соавт.…”
Section: надлобковый доступunclassified
See 1 more Smart Citation
“…
Dear Editor, We thank Professor Wiwanitikit for his letter [1] regarding our recent publication [2]. In answer to his queries, we feel that the visual analogue scale (VAS) for urgency is a subjective measure of sensory function as felt by the patient.
…”
mentioning
confidence: 99%